2014
DOI: 10.1111/eje.12113
|View full text |Cite
|
Sign up to set email alerts
|

Service‐learning's impact on dental students' attitude towards community service

Abstract: Introduction This study evaluated service-learning program’s impact on senior dental students’ attitude toward community service at Virginia Commonwealth University (VCU) School of Dentistry. Experience gained through service-learning in dental school may positively impact dental students’ attitude toward community service that will eventually lead into providing care to the underserved. Materials and methods Two surveys (pre and post-test) were administered to 105 senior dental students. For the first surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 27 publications
(44 reference statements)
0
29
0
3
Order By: Relevance
“…Another study done by Fitch N.,[23] reported 96% of the participants became more aware of the needs of communities. Similarly a study done by Coe et al ,[24] reported that 63% more students participated in the community services and developed the need for it and Nowaiser et al ,[25] reported 80% of the respondents agreed that the dental community field experience made them aware of their roles, responsibilities toward the community and population needs.…”
Section: Discussionmentioning
confidence: 82%
“…Another study done by Fitch N.,[23] reported 96% of the participants became more aware of the needs of communities. Similarly a study done by Coe et al ,[24] reported that 63% more students participated in the community services and developed the need for it and Nowaiser et al ,[25] reported 80% of the respondents agreed that the dental community field experience made them aware of their roles, responsibilities toward the community and population needs.…”
Section: Discussionmentioning
confidence: 82%
“…No estudo realizado em uma universidade norte americana, os pesquisadores ressaltaram que a vivência dos alunos com os problemas bucais reais da comunidade a qual estão inseridos, gera reflexões sobre a problemática enfrentada e a conscientização das diversidades culturais e étnicas 21 . Coe et al 22 ao empregar uma metodologia para analisar como o programa de ensino-serviço realizado na Virginia-EUA interfere na atitude dos acadêmicos para atenção a saúde bucal, concluíram que as atividades executadas tiveram impactos positivos em algumas dimensões, gerando benefícios para os participantes envolvidos. Pesquisas nacionais enfatizam as experiências e percepções dos graduandos sobre as atividades extramurais, e ressaltam a valorização dessa atividade para o comprometimento e engajamento dos discentes com as práticas de ensino, sendo o contato direto com a realidade e o contexto social, a principal característica de agregação de experiência profissional 5,7,23,24 .…”
Section: Resultsunclassified
“…9,[11][12][13]17 The benefits of SL have included but are not limited to professional and doctor-patient communication, cultural competence/awareness, connectedness, normative helping behavior, career benefits, changes in knowledge and attitudes about older adults, awareness of service-providing agencies and community needs, increased awareness of the importance of public health, clinical confidence, utility of history and examination, transformational change, and a reported increase in positive influence on clinical skills 2 years post trip. 9,11,12,[17][18][19] Educational outcomes for SL have been suggested such as personal and interpersonal development, understanding and applying knowledge, engagement curiosity and reflective practice, critical thinking, perspective transformation, and citizenship. 20 Reflection of the experience is a key learning objective to achieve maximal educational benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Service learning (SL) courses, defined as combining student educational goals with community needs, [9][10][11][12][13] are thought to provide students with the opportunity to gain clinical confidence in their respective fields. There is a paucity of evidence pertaining to SL in the chiropractic literature.…”
Section: Introductionmentioning
confidence: 99%